2019
DOI: 10.1021/jacs.9b04702
|View full text |Cite
|
Sign up to set email alerts
|

A Chlorine-Atom-Controlled Terminal-Epoxide-Initiated Bicyclization Cascade Enables a Synthesis of the Potent Cytotoxins Haterumaimides J and K

Abstract: Haterumaimide J (hatJ) is reportedly the most cytotoxic member of the lissoclimide family of labdane diterpenoids. The unusual functional group arrangement of hatJ-C18 oxygenation and C2 chlorination-resisted our efforts at synthesis until we adopted an approach based on rarely studied terminal epoxide-based cation-π bicyclizations that is described herein. Using the C2chlorine atom as a key stereocontrol element and a furan as a nucleophilic terminator, the key structural features of hatJ were rapidly constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Although biosynthetically the oxidation of this carbon center surely occurs post‐cyclization, it would be strategically valuable to incorporate these functional groups prior to cyclization in the laboratory setting. This idea is in line with our broader program to extend the range of functionalized substrates in stereocontrolled polycyclizations . We presumed that this C20 “handle” would prove advantageous in subsequent applications to molecules such as 1 , 2 , and the many other diterpenoids with an oxidized C20 that is also frequently part of a ring structure.…”
Section: Introductionmentioning
confidence: 65%
“…Although biosynthetically the oxidation of this carbon center surely occurs post‐cyclization, it would be strategically valuable to incorporate these functional groups prior to cyclization in the laboratory setting. This idea is in line with our broader program to extend the range of functionalized substrates in stereocontrolled polycyclizations . We presumed that this C20 “handle” would prove advantageous in subsequent applications to molecules such as 1 , 2 , and the many other diterpenoids with an oxidized C20 that is also frequently part of a ring structure.…”
Section: Introductionmentioning
confidence: 65%
“…Coupling of allylic bromide (+)- 20 (93% ee) with the organolithium reagent derived from treatment of 18 with n -BuLi proceeded smoothly to give epoxide 17 in 87% yield . After extensive optimization, we were pleased to find that by exposure of 17 to BF 3 ·OEt 2 in toluene at −78 °C for 1 h, the desired tricycle 21 could be obtained in 45% yield. ,, As a comparison, other Lewis acids such as Et 2 AlCl, TiCl 4 , InBr 3 , FeCl 3 , Bi­(OTf) 3 , TMSOTf, and Ph 4 PBF 4 either gave no reaction or caused significant decomposition of the starting material. Under Mitsunobu conditions, the hydroxyl group at C3 was successfully eliminated to produce the corresponding alkene, which then underwent dedithianation at C7 with PhI­(CF 3 CO 2 ) 2 and CaCO 3 at 0 °C to deliver ketone 22 in 74% yield over two steps.…”
mentioning
confidence: 99%
“…Theu se of substoichiometric quantities of oxidant was not tolerated (entry 2), and different silanes, including the "Ruben-silane" [14] (entries 3a nd 4), did not significantly improve the outcome.F or its convenience and low price,TMDSO was chosen as the preferred silane.Other single-electron oxidants,including Cu(OTf) 2 and CAN, led to decomposition (not shown, see the Supporting Information). Fortuitously,asmall solvent screen revealed that carrying out the reaction in HFIP led to significantly improved yields (entries [4][5][6][7][8]. Ascreen of afew different catalysts (entries 8-10) revealed that only C1 gave full conversion in 3hours.…”
Section: Resultsmentioning
confidence: 99%
“…Although biosynthetically the oxidation of this carbon center surely occurs post-cyclization, it would be strategically valuable to incorporate these functional groups prior to cyclization in the laboratory setting.T his idea is in line with our broader program to extend the range of functionalized substrates in stereocontrolled polycyclizations. [7] We presumed that this C20 "handle" would prove advantageous in subsequent applications to molecules such as 1, 2,a nd the many other diterpenoids with an oxidized C20 that is also frequently part of aring structure.These synthesis endeavors themselves were largely discouraged by recent attractive, closely related successes by Li and co-workers, [8] who included as econdary allylic ether function at this position in aC arreira-type enantioselective polycyclization, [4b] and Ma and coworkers, [9] who used ad ifferent scaffold-building strategy to make nitrile compounds related to 4b.H owever,a so ur studies unfolded, we were surprised to discover conditions for Co-catalyzed HAT-initiated (HAT = hydrogen-atom transfer) dialkenylarene bicyclizations with ar ather broad scope, including the intriguing tolerance of either aC 20 electrondonating methyl group (3a)o ra ne lectron-withdrawing nitrile (3b). These results and some preliminary mechanistic investigations are the subject of this report.…”
Section: Introductionmentioning
confidence: 99%